Distinguishing direct from indirect roles for bicoid mRNA localization factors. - Weil, T; Xanthakis, D; Parton, R; Dobbie, I; Rabouille, C; Gavis, E; Davis, I (2010)
Localization of bicoid mRNA to the anterior of the Drosophila oocyte is essential for patterning the anteroposterior body axis in the early embryo. bicoid mRNA localizes in a complex multistep process involving transacting factors, molecular motors and cytoskeletal components that remodel extensively during the lifetime of the mRNA. Genetic requirements for several localization factors, including Swallow and Staufen, are well established, but the precise roles of these factors and their relationship to bicoid mRNA transport particles remains unresolved. Here we use live cell imaging, super-resolution microscopy in fixed cells and immunoelectron microscopy on ultrathin frozen sections to study the distribution of Swallow, Staufen, actin and dynein relative to bicoid mRNA during late oogenesis. We show that Swallow and bicoid mRNA are transported independently and are not colocalized at their final destination. Furthermore, Swallow is not required for bicoid transport. Instead, Swallow localizes to the oocyte plasma membrane, in close proximity to actin filaments, and we present evidence that Swallow functions during the late phase of bicoid localization by regulating the actin cytoskeleton. In contrast, Staufen, dynein and bicoid mRNA form nonmembranous, electron dense particles at the oocyte anterior. Our results exclude a role for Swallow in linking bicoid mRNA to the dynein motor. Instead we propose a model for bicoid mRNA localization in which Swallow is transported independently by dynein and contributes indirectly to bicoid mRNA localization by organizing the cytoskeleton, whereas Staufen plays a direct role in dynein-dependent bicoid mRNA transport.